새만금간척지 조기노출지역의 담수기간별 제염과 청보리 생육 - 최원영; Weon-young Choi; 송태화; Tae-hwa Song; 김선; Sun Kim; 이장희; Jang-hee Lee; 정재혁; Jae-hyeok Jeong; 김시주; Si-ju Kim; et al. (Korean journal of crop science, 2013)
This study was conducted to investigate upland crop at reclaimed sand land 'Saemangeum' for early desalination purpose and to investigate the growth and yield of whole crop barley, which was acceded after summer crop of corn and rice. Seedling establishment of whole crop barley were 216 seedlings/㎡(25%) for non-flooding, 43% for 1 month and 58% for 2, 3 month flooding. And it was 60% in rice cultivation. Soil salt concentration was 0.5% in non-flooding treatment, however flooding treatments decreased to 0.2% or less. In general soil salt concentration increased until the middle stage of growing, then became to similar level as the seeding time. Plant height, stem length and number of tiller were increased with flooding treatment. Whole crop barley yield was significantly reduced in non-flooding treatment but rapidly increased by flooding treatment. Yielding at 3 months increased by 504% compared to non-flooding, and rice cultivation was also increased by 536%. Protein and fiber content was low in 1 month flooding treatment, 3 months flooding and rice cultivation showed the similar results in terms of feed value. For desalination purpose in reclaimed land, 3 months flooding treatments of rice cultivation could result in higher yielding for upland crop, such as whole crop barley.